Marine High Resolution Records of the Last Interglacial in Northwest Europe: A Review - Seidenkrantz, Marit-Solveig; Knudsen, Karen (Géographie physique et Quaternaire, 1994)
ABSTRACTThe last Interglacial in Northwest Europe (the Eemian) corresponds to stable oxygen isotope substage 5e (ca. 130-115 ka BP). Foraminiferal studies from northern Denmark suggest that déglaciation after the Saalian Glacial (stage 6) occurred gradually over a period of about 3000 years. Data from borings on the island of Anholt show that the déglaciation was interrupted by a climatic fluctuation equivalent to the Allerod-Younger Dryas-Preboreal cycle at the Weichselian-Holocene transition (stage 2/1). The environmental interpretation of the foraminiferal data when compared to that of the deep sea stable isotope stratigraphy indicates that this climatic oscillation may have been a global event. An initial sea level rise of about 50-60 m occurred at the Saalian-Eemian transition (stage 6/5e at about 130 ka BP) and the assemblages indicate that the sea level rose further in the middle part of the Eemian prior to a gradual drop in sea level in the Late Eemian. The Eemian/ Weichselian boundary (stage 5e/5d at about 115 ka BP) was characterized by a major sea level drop and a temperature decrease from lusitanian to boreal conditions. The final change to fully glacial conditions did not occur until the Early-Middle Weichselian transition (stage 5/4 at about 74 ka BP).